Osteogenic differentiation of human bone marrow mesenchymal stem cells in hydrogel containing nacre powder. Issue 11 (3rd April 2013) - Flausse, Alicia; Henrionnet, Christel; Dossot, Manuel; Dumas, Dominique; Hupont, Sébastien; Pinzano, Astrid; Mainard, Didier; Galois, Laurent; Magdalou, Jacques; Lopez, Evelyne; Gillet, Pierre; Rousseau, Marthe
<x xml:space="preserve">Abstract</x> Nacre (or mother of pearl) can facilitate bone cell differentiation and can speed up their mineralization. Here we report on the capability of nacre to induce differentiation of human bone marrow mesenchymal stem cells (hBM‐MSCs) and the production of extracellular matrix. hBM‐MSCs were encapsulated in an alginate hydrogel containing different concentrations of powdered nacre and cultured in the same environment until Day 28. Analysis of osteogenic gene expression, histochemistry, second harmonic generation (SHG) microscopy, and Raman scattering spectroscopy were used to characterize the synthesis of the extracellular matrix. In the presence of nacre powder, a significant increase in matrix synthesis from D21 in comparison with pure alginate was observed. Histochemistry revealed the formation of a new tissue composed of collagen fibers in the presence of nacre (immunostaining and SHG), and hydroxyapatite crystals (Raman) in the alginate beads. These results suggest that nacre is efficient in hBM‐MSCs differentiation, extracellular matrix production and mineralization in alginate 3D biomaterials. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 101A: 3211–3218, 2013.